Challenges in enabling privacy self management - Vidhani, Kumar; Banahatti, Vijayanand; Lodha, Sachin (CSI TRANSACTIONS ON ICT, 2021)
From being a set of desirable principles to the legal binding requirement, privacy has come off age. Newer privacy regulations demand enterprises to inculcate privacy-by-design principles. Importantly, they are mandating enterprises to implement privacy self management paradigm that empowers data subjects with control and rights over their data. This paradigm shift has brought in a major disruption and created multiple challenges for enterprises and data subjects. In this article, we first highlight the challenges faced by enterprises with respect to data, applications and technology. Here we describe the problems pertaining to both structured and unstructured data. Then we discuss issues in bringing enterprise legacy systems up to speed as well as some potential challenges for greenfield applications while following the privacy-by-design principles. We also outline problems that enterprises need to pay attention to while adopting some of the latest technologies, namely, Cloud, Artificial Intelligence and Internet of Things. Subsequently, we discuss multiple challenges from data subject’s perspective. We particularly deliberate on the lack of standardization of privacy policy, consent fatigue, inappropriate consent and granularity of data sharing challenges. Lastly, we briefly outline four core principles that could serve enterprise to create an effective, rewarding and futuristic privacy program.